2016
DOI: 10.12968/ijpn.2016.22.8.396
|View full text |Cite
|
Sign up to set email alerts
|

Carer experiences of inpatient hospice care for people with dementia, delirium and related cognitive impairment

Abstract: The findings suggest that carer confidence is enhanced by: staff awareness and response to individual patient needs, interests and preferences, as well as carer requirements for information and consultation; an environment that engenders experience of comfort, safety, flexibility, privacy and outdoor connection; carer preparedness for patients who subsequently transition home or to alternative residential care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…Unfortunately, few qualitative studies exist on perceived care at residential hospices that could be compared to our findings. An in-depth study of caregivers ( n = 10) of patients in a hospice in New Zealand found that these experiences were characterized by staff being attuned to individual patients' needs and preferences in an environment that engenders qualities similar to those found in our study (Bolton et al, 2016). A recent meta-synthesis of the palliative care experience in hospital, based on patient and caregiver narratives from 16 studies, identified 6 essential themes, seemingly applicable to all care settings: expert care, effective communication and shared decision making, respectful and compassionate care, adequate environment for care, family involvement, and financial affairs (Virdun et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…Unfortunately, few qualitative studies exist on perceived care at residential hospices that could be compared to our findings. An in-depth study of caregivers ( n = 10) of patients in a hospice in New Zealand found that these experiences were characterized by staff being attuned to individual patients' needs and preferences in an environment that engenders qualities similar to those found in our study (Bolton et al, 2016). A recent meta-synthesis of the palliative care experience in hospital, based on patient and caregiver narratives from 16 studies, identified 6 essential themes, seemingly applicable to all care settings: expert care, effective communication and shared decision making, respectful and compassionate care, adequate environment for care, family involvement, and financial affairs (Virdun et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…The 16 studies were based in Australia ( n = 4), 22 , 23 , 36 39 Canada ( n = 4), 40 44 UK ( n = 2), 45 , 46 USA ( n = 2), 47 , 48 Japan ( n = 2), 49 , 50 Israel ( n = 1) 51 53 and New Zealand ( n = 1). 54 Three of the studies were conducted by co-authors of this review. 23 , 37 39 , 41 The majority of studies were conducted in palliative care inpatient settings, including seven based only in hospital inpatient units 22 , 23 , 37 39 , 41 , 42 , 48 , 51 53 and six based only in hospice inpatient units.…”
Section: Resultsmentioning
confidence: 99%
“…Person-centred care, communication and challenges: Clinicians described taking a person-centred approach to care for patients with delirium, 23,43,44,46,50,54 "I love the whole approach and it is holistic in here -we look at the whole patient and everything that makes a difference." 46 (Nurse, p.531)…”
Section: Trustworthiness Of Findingsmentioning
confidence: 99%
“…However, the response patterns for two items did not accord with Rasch expectations, and so were removed in the PCQ-S-R. Item 1 (‘a place where I feel welcome’) was removed, which might be of some concern given this has been identified as an important aspect of service user and carer experience, at least in hospital settings [42]. Arguably, the notion of ‘feeling welcome’ is pertinent in joining new environments that is not one’s own, and may be less suited to long-term residential settings where some will have been resident for many months and years.…”
Section: Discussionmentioning
confidence: 99%